2020
DOI: 10.1186/s40779-020-00285-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects and mechanism of platelet-rich plasma on military drill injury: a review

Abstract: Military drill injury is a significant part of military medical research. The increase of training intensity and changes in training methods lead to differences in injury types. The ideal therapeutic modality should allow rapid healing at a reasonable cost and minimize impact on patients’ life. Platelet -rich plasma (PRP), a platelet concentrate, is rich in a variety of growth factors and widely used clinically as a minimally invasive treatment. It plays an important role in injury repair and rehabilitation. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Bioelectrical impedance analysis-guided fluid resuscitation in post-traumatic open abdomen patients managed to achieve a higher primary fascial closure rate and fewer complications compared to traditional resuscitation strategy [50]. In the military setting, Xu et al [51] reviewed the literature on the role of platelet-rich plasma (PRP) on military drill injury, as well as discussed the pros and cons and surrounding controversies of PRP therapy. While there seems to be existing limitations to the use of PRP, the minimally-invasive nature of the treatment and its potential benefits make it an attractive option in the therapeutic armamentarium.…”
Section: Advances In Wound Healingmentioning
confidence: 99%
“…Bioelectrical impedance analysis-guided fluid resuscitation in post-traumatic open abdomen patients managed to achieve a higher primary fascial closure rate and fewer complications compared to traditional resuscitation strategy [50]. In the military setting, Xu et al [51] reviewed the literature on the role of platelet-rich plasma (PRP) on military drill injury, as well as discussed the pros and cons and surrounding controversies of PRP therapy. While there seems to be existing limitations to the use of PRP, the minimally-invasive nature of the treatment and its potential benefits make it an attractive option in the therapeutic armamentarium.…”
Section: Advances In Wound Healingmentioning
confidence: 99%
“…21 Upon activation, these platelets release an array of growth factors and cytokines. 22 Remarkably, PRP inherently serves as a growth factor carrier, negating the need for external mediums. 2 Bones, naturally endowed with a potent regenerative capacity, utilize cellular components, growth factors, and elements of the extracellular matrix for restoratio.…”
Section: Growth Factor Dynamics Of Prp In Osteogenesismentioning
confidence: 99%
“…Therefore, a new therapeutic tool, platelet-rich plasma (PRP) technology, has been developed because of the presence of large amounts of GFs in platelets, which can be used for DU repair. PRP is a platelet concentrate obtained by centrifugation of a patient's fresh peripheral blood [ 259 ]. Wei et al loaded PRP into an ODex, antimicrobial peptide-modified hyaluronic acid (HA-AMP) hydrogel and confirmed that the hydrogel can promote the proliferation and migration of L929 fibroblasts through CCK-8 assays, live/dead fluorescent staining and scratch tests.…”
Section: Bioactivators For Dusmentioning
confidence: 99%